AN ADAPTIVE ROLE-BASED ACCESS CONTROL APPROACH FOR CLOUD E-HEALTH SYSTEMS - Al-Badarneh, Amer; Najadat, Hassan; ’Hassan Abu Yabes’, Enas (LIFE: International Journal of Health and Life-Sciences, 2017)
Securing and protecting electronic medical records (EMR) stored in a cloud is one of the most critical issues in e-health systems. Many approaches with different security objectives have been developed to adapt this important issue.This paper proposes a new approach for securing and protecting electronic health records against unauthenticated access with allowing different hospitals, health centres and pharmacies access the system, by implementing role-based access control approach that could be applied smoothly in cloud e-health systems.